2011
DOI: 10.1002/prot.23045
|View full text |Cite
|
Sign up to set email alerts
|

Observing the osmophobic effect in action at the single molecule level

Abstract: Protecting osmolytes are widespread small organic molecules able to stabilize the folded state of most proteins against various denaturing stresses in vivo. The osmophobic model explains thermodynamically their action through a preferential exclusion of the osmolyte molecules from the protein surface, thus favoring the formation of intrapeptide hydrogen bonds. Few works addressed the influence of protecting osmolytes on the protein unfolding transition state and kinetics. Among those, previous single molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
(126 reference statements)
4
13
1
Order By: Relevance
“…In our studies of urea and GuHCl in the submolar concentration range, we did not see a significant effect on binding to the unfolded polyprotein. This may indicate the binding is too weak at these concentrations, which is consistent with previous works showing that urea and GuHCl decrease the mechanical stability of the folded protein domains only at concentrations in the molar range (51)(52)(53)(54)(55).…”
Section: Discussionsupporting
confidence: 90%
“…In our studies of urea and GuHCl in the submolar concentration range, we did not see a significant effect on binding to the unfolded polyprotein. This may indicate the binding is too weak at these concentrations, which is consistent with previous works showing that urea and GuHCl decrease the mechanical stability of the folded protein domains only at concentrations in the molar range (51)(52)(53)(54)(55).…”
Section: Discussionsupporting
confidence: 90%
“…Herein we show that the same lack of movement holds for various concentrations of DMSO and GndCl, indicating that osmolytes may not generally produce significant movements of the unfolding transition states of proteins. Furthermore, we expand the mentioned thermodynamic analysis with mechanical unfolding simulations based on the worm-like-chain (WLC) force-distance relation (12,13), showing that our Ising-like model exhibits no significant change in the unfolding distance of GB1 and I27 under the effect of various concentrations of DMSO, glycerol, and GndCl, in excellent agreement with the experimental results presented herein and those of Aioanei et al (9,10) and Cao and Li (11). Note that our Ising-like model lacks the expressive power to account for any possible structural role of osmolytes at the unfolding transition state of proteins, while still being able to explain the mentioned experimental data.…”
Section: Introductionsupporting
confidence: 87%
“…Theoretically, we have recently shown that an Ising-like model with support for the osmolyte effect does not exhibit any movement of the unfolding transition state of GB1 in the presence of glycerol 30% v/v, when projected thermodynamically onto a commonly used nonmechanical reaction coordinate (10). Herein we show that the same lack of movement holds for various concentrations of DMSO and GndCl, indicating that osmolytes may not generally produce significant movements of the unfolding transition states of proteins.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Reduction in osmolyte concentration in the immediate vicinity of the protein cannot be described solely based on the effect of the excluded volume, as in this case, the action of osmoprotectors on protein stability would be determined exclusively by the size of the osmolyte molecules [36]. An osmophobic character of the interactions of some osmolytes with a number of proteins has been shown experimentally [37,38]. It should be noted that introduction of osmolytes into solution under conditions of their exclusion from the immediate vicinity of the protein increases the chemical potential of the systems, i.e., it destabilizes it [25][26][27][28].…”
Section: Osmolytes Of Class II Increase (mentioning
confidence: 96%